Macroprudential Policies and House Prices in Europe - Arena, Marco (Departmental Papers; Departmental Paper ;, 2020)
Macroprudential policy in Europe aligns with the objective of limiting systemic risk, namely the risk of widespread disruption to the provision of financial services that is caused by an impairment of all or parts of the financial system and that can cause serious negative consequences for the real economy.